2009
DOI: 10.4315/0362-028x-72.4.810
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Response to Puffer Fish (Tetrodotoxin) Poisoning from Mislabeled Product

Abstract: Tetrodotoxin is a neurotoxin that occurs in select species of the family Tetraodontidae (puffer fish). It causes paralysis and potentially death if ingested in sufficient quantities. In 2007, two individuals developed symptoms consistent with tetrodotoxin poisoning after ingesting home-cooked puffer fish purchased in Chicago. Both the Chicago retailer and the California supplier denied having sold or imported puffer fish but claimed the product was monkfish. However, genetic analysis and visual inspection dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(92 citation statements)
references
References 21 publications
0
87
0
2
Order By: Relevance
“…The extent of this phenomenon on the global market of fresh, smoked or dried fish products varies across continents [20,[49][50][51] and the possible explanations include genuine mislabeling due to morphological similarities between closely related species or fraudulent substitution of expensive species with cheaper variants. An extreme case of fish substitution had drastic consequences for public health, leading to food poisoning due to puffer fish toxin and the consequent recall of products [52]. With its power to reveal mislabeled products, DNA barcoding will have multiple implications from food safety and public health, to fisheries management (depletion of fish stocks) and conservation (protected species caught illegally).…”
Section: Practical Applications For the Marine Environmentmentioning
confidence: 99%
“…The extent of this phenomenon on the global market of fresh, smoked or dried fish products varies across continents [20,[49][50][51] and the possible explanations include genuine mislabeling due to morphological similarities between closely related species or fraudulent substitution of expensive species with cheaper variants. An extreme case of fish substitution had drastic consequences for public health, leading to food poisoning due to puffer fish toxin and the consequent recall of products [52]. With its power to reveal mislabeled products, DNA barcoding will have multiple implications from food safety and public health, to fisheries management (depletion of fish stocks) and conservation (protected species caught illegally).…”
Section: Practical Applications For the Marine Environmentmentioning
confidence: 99%
“…In addition, DNA barcoding strategies are now being applied for other groups of organisms including plants (CBOL Plant Working Group 2009;Goa et al 2010), macroalgae (Saunders 2005), fungi (Seifert et al 2007;Stockinger et al 2010), protists (Chantangsi et al 2007), and bacteria (Sogin et al 2006). Furthermore, DNA barcoding has gained wide application in forensic analysis to investigate cases of illegal poaching (Eaton et al 2009), separation of species (Wilson-Wilde et al 2010), gut content analysis in ecological studies (Smith et al 2005;Berry et al 2007;Clare et al 2009), food product analysis and market substitution (Wong and Hanner 2008;Cohen et al 2009), and Asian medicine trade regulation (Peppin et al 2008). DNA barcoding has also been employed to validate the identity of biomaterial collections and cell lines (Lorenz et al 2005;Cooper et al 2007).…”
mentioning
confidence: 99%
“…And previous studies showed that chloroform may be used as defating agent in reflux defatting technique (Cohen et al 2009;Schober et al 2010). Here, dried powder of SFSEB (5.0 g) was placed into 50 mL of chloroform and refluxed for 2 h at 60°C for defatting.…”
Section: Methodsmentioning
confidence: 99%